Phylogeny and reclassification of Distictus Townes (Hymenoptera, Ichneumonidae, Cryptinae), with description of a new species - Santos, Bernardo F.; Aguiar, Alexandre P. (Zootaxa, 2008)
Distictus aurantium new species, from the Brazilian Atlantic Forest, is described and illustrated. The validity of Distictus Townes was cladistically tested against 19 species and 60 informative characters, both with implied weighting and unweighted analyses. All cladograms recovered Distictus as monophyletic, while suggesting that it might be the sister group of the clade Lagarosoma Gupta + Prosthoporus Porter + Trypha Townes. Fenixia Aguiar is proposed as a new junior synonym of Distictus Townes, and the valid genus is transferred from Cryptina (=Ischnina) to Gabuniina. New distribution records expand the known range of D. tibialis to 17º48' latitude degrees, from Rio Grande do Sul to Goiás (Brazil).